Anti-tumor and chemosensitization effects of Cryptotanshinone extracted from Salvia miltiorrhiza Bge. on ovarian cancer cells in vitro. (9th June 2017) - Jiang, Guoqiang; Liu, Jia; Ren, Baoyin; Zhang, Lin; Owusu, Lawrence; Liu, Likun; Zhang, Jing; Tang, Yawei; Li, Weiling
Abstracts: Ethnopharmacological relevance: Cryptotanshinone, a natural compound isolated from the roots of Salvia miltiorrhiza Bge. (Danshen), is a commonly used traditional Chinese medicine to treat high blood pressure in some countries. It has been shown that Cryptotanshinone induces cancer cells apoptosis and impairs cell migration and invasion. However, the antiproliferation and chemosensitization effects of Cryptotanshinone on ovarian cancer and the underlying mechanism are not fully elucidated. Aim of study: In this study, we evaluated the inhibitory effect of Cryptotanshinone on ovarian cancer cells and explored the underlying molecular mechanism. Additionally, the chemosensitization potential of Cryptotanshinone was evaluated in combination with cisplatin. Materials and methods: MTT assay was used for cell viability assessment of ovarian cancer A2780 cells treated with Cryptotanshinone and/ or cisplatin. Flow cytometry was used for apoptosis analysis. Wound healing and transwell assays were used for migratory and invasive potential assessment of Cryptotanshinone-treated ovarian cancer cells. Western blot was used to investigate proteins involved in the mechanisms for metastasis and apoptosis. γH2AX immunocytochemistry was used to detect DNA damage in A2780 cells exposed to Cryptotanshinone and/or cisplatin. Results: Cryptotanshinone significantly induced ovarian cancer A2780 cells apoptosis by activating caspase cascade. Additionally, wound healing and transwell assays revealed that Cryptotanshinone could suppress migration and invasion of ovarian cancer cells and dramatically inhibited MMP-2 and MMP-9 expression. Furthermore, Cryptotanshinone could sensitize A2780 cells to cisplatin treatment in a dose-dependent manner. Conclusion: Our data confirmed the anti-tumor effect of Cryptotanshinone on ovarian cancer cells and provided new findings that Cryptotanshinone could sensitize ovarian cancer cells to chemotherapy. Graphical abstract: